Electric-field-induced avalanches and glassiness of mobile ferroelastic twin domains in cryogenic SrTiO_{3} - Blai Casals; Sebastiaan van Dijken; Gervasi Herranz; Ekhard K. H. Salje (Physical Review Research, 2019)
Domain motion during ferroelectric switching has been recently suggested to follow scale-invariant avalanche dynamics. An interesting question concerns the dynamics of ferroelastic materials where the bulk material is nonpolar, while the polarity arises at domain walls only. We tackle this issue by investigating the dynamics of ferroelastic twins in SrTiO_{3} where the movement of domains is driven mainly by the anisotropic dielectric response at low temperatures. We find that the dynamics of the twin reconfiguration under electric field proceeds by jerks, where the energy distribution is power-law distributed, indicating avalanche dynamics. Avalanche exponents are sensitive to the complexity of the twin pattern structure, reflecting glassiness when twins are interwoven and forming junctions at the intersections between domain walls. This “glassy” behavior is attributed to the pinning originated by these self-generated defects during jamming between twins.